WILLIS, David, Christopher LUCAS and Anne BREITBARTH (ed.): The History of Negation in the Languages of Europe and the Mediterranean. Vol. I: Case Studies. Oxford: Oxford University Press, 2013. 560 p., ISBN 978-0-19-960253-7 - Zovko Dinković, Irena (Array, 2014)
This book is the first in a two-volume comparative history of negation in the languages of Europe and the Mediterranean, published as part of the series Studies in Diachronic and Historical Linguistics – aimed at publishing high-quality studies of language change, which also make a significant contribution to linguistic theory by developing theoretical connections with other areas of linguistics and cognitive science. This and the forthcoming volume present the findings of the project The development of negation in the languages of Europe. This first volume is thoroughly empirical in scope and aims at providing a detailed account of changes in the expression of negation and indefinites in the languages of Europe and the Mediterranean.